RI 3892 Studies on the Flotation of Spodumene from the Edison Mine, Keystone, South Dakota - Gerald A. Munson; K. L. Erickson (The National Institute for Occupational Safety and Health (NIOSH), 1946)
"The need for spodumene as a source of lithia for war purposes led to the exploitation of the Edison pegmatite deposit 1-1/2 miles southeast of Keystone, S. Dak. The operation was conducted during 1943 and 1944 by the Lor Mining Co., Rapid City, S. Dak. Spodumene concentrates in the ratio of 15:1 were recovered by hand picking from a sorting belt. This method was expensive and wasteful of spodumene, owing to the small size of the crystals.Data4/ obtained by the Bureau of Mines indicates that blunging with hydroflouric acid or sodium hydroxide is a prerequisite to selective flotation. Results of tests by Denver Equipment Co., Denver, Colo., indicate that economic recoveries can be obtained in an alkaline circuit after desliming.At the request of the Lor Mining Co., K. L. Erickson, metallurgical engineer, was permitted to work in the pegmatite research laboratory to verify previous investigations and to determine problems that might be involved in commercial milling. The ensuing investigation indicated that electrolytes in the mill water produced a profound inhibiting action on the flotation of Edison spodumone.An investigation of mill water from various sources showed that some waters are suitable for the process and others are not. Subsequent testing showed that all of the available waters are suitable after treatment. The flotation of the Edison spodumene in an alkaline circuit after desliming and using oleic acid as collector is efficient and economical when the water does not contain impurities.In its program of exploration of mineral deposits, the Bureau of Mines has as its primary objective the more effective utilization of our mineral resources to the end that they make the greatest possible contribution to national security and economy. It is the policy of the Bureau to publish the facts developed by each exploratory project as soon as practicable after its conclusion. The Mining Branch, Lowell B.Moon, chief, conducts preliminary examinations, performs the actual exploratory work, and prepares the final report. The Metallurgical Branch, R. G. Knickerbocker, chief, analyzes samples and performs beneficiation tests. Both these branches arc under the supervision of Dr. R. S. Dean, assistant director.As the work was of a practical nature, samples from possible mill-water sources in the southern Black Hills were obtained, and commercial softening and demineralizing methods were investigated. Data on various waters tested are given in table 1."